Constraint exploration method for quadratic programming problem - Mohd, Ismail; Dasril, Yosza (2000)
In this paper, we represent a method which is based on the violated constraints by the unconstrained minimum of the objective function of the quadratic programming problem for exploring, locating and computing the optimal solution of the problem without using additional information as have been done in most of the favourite established methods.